Assessment of Practice and Factors associated with Sunlight Exposure of Infants among Mothers in Debre Berhan Town, North Shewa Zone, Amhara Region, Ethiopia - Teklehaimanot WZ; Kitawu LD; Tesfaye T; Mihretie A; Tizazu MA; Mekuriyaw AM; Negash KM; Muluneh MA (Dove Medical Press, 2021)
Wegayehu Zeneb Teklehaimanot,1 Leul Deribe Kitawu,2 Tewodros Tesfaye,2 Abebe Mihretie,1 Michael Amera Tizazu,1 Abebayehu Melesew Mekuriyaw,1 Kassa Mamo Negash,1 Mikyas Arega Muluneh1 1College of Health Science, Debre Berhan University, Debre Berhan, Ethiopia; 2College of Health Science, Addis Ababa University, Addis Ababa, EthiopiaCorrespondence: Wegayehu Zeneb Teklehaimanot Tel +251 912768453Email wegayehuzeneb@gmail.comBackground: Vitamin D deficiency is a common worldwide problem with its prevalence magnified in infants. Prevalence in infants is believed to range from 2.7% to 45% in different countries of the world. Appropriate sunlight exposure of skin is thought to be vital for the prevention of vitamin D deficiency. However, due to a dearth of study the practice of sunlight exposure is incompletely understood. Thus, assessing practice and factors affecting sunlight exposure of infants by mothers was relevant.Objective: To assess practice level and factors associated with sunlight exposure of infants by mothers in Debre Berhan town, North Showa, Ethiopia, 2019.Materials and Methods: A community-based cross-sectional study was conducted to collect relevant data among 530 mothers with infants at selected kebeles in Debre Berhan town. A simple random sampling technique was used to select kebeles and systematic sampling was complemented to identify study participant. Data were collected with interview using a pre-tested structured and semi-structured questionnaire. Bivariable and multivariable logistic regressions were run to examine the association among dependent and independent variable. Significant association was declared at P value ≤ 0.05.Results: All the mothers were interviewed and 65.7% of them had good practice in sunning of their infant. In multi-variable analysis, mothers who are housewives or government employees, have a maternal age of 33 and above, perceive that sunlight strengthen infant bones, perceive that sunlight makes their infants healthier, and who got information from health-care professionals were significantly associated with good practice in sunning of their infant.Conclusion and Recommendation: Finding of this study indicated that 34.3% of participants have poor practice in sunning of infants. This is a pointer that sunlight exposure of infants still needs attention from the government and other concerned bodies.Keywords: rickets, sunlight exposure, ultraviolet index, vitamin D, VDD